Numerical simulation of gas extraction performance from hydrate reservoirs using double-well systems. (15th February 2023) - Dong, Lin; Li, Yanlong; Wu, Nengyou; Wan, Yizhao; Liao, Hualin; Wang, Huajian; Zhang, Yajuan; Ji, Yunkai; Hu, Gaowei; Leonenko, Yuri
Abstract: Multi-well systems can increase the drainage area and hence enhance the productivity of natural gas hydrate (NGH) production. Fundamentally, the double-well system is the key and basis of understanding the multi-well system and formulating field strategies for gas extraction from hydrate-bearing sediments. However, production performance and multi-well production strategies for recovering NGH by using depressurization have not been treated in detail. Here we develop a three-dimensional model to describe double-well production characteristics from the low-permeability hydrate reservoir and analyze well-deployment strategies. The productivity of this double-well system is 1.5–2.5 higher than that of the single well under the same conditions, which is triggered by enlarging the drainage area. The well spacing alters flow characteristics and corresponding geophysical fields, which is the key variable for the double-well system in gas recovery. Its range can be determined based on the combination of productivity and hydrate dissociation front. Besides, due to the limited enhancement in productivity using the double-well system, the multi-well system assisted with reservoir reconstruction technologies and stimulation methods is of significant practical value in realizing commercial exploitation of NGH. Highlights: Propose a 3D thermal-hydro-chemical coupling model for production using double-well systems. Gas extraction performance and reservoir responses are investigated. Effects of well spacing on productivity and physical fields are analyzed. Discuss production strategies of multi-well systems considering commercial hydrate production.